Regulatory T Cells as Immunotherapy - Singer, Benjamin D.; King, Landon S.; D'Alessio, Franco R. (Frontiers in Immunology, 2014)
Regulatory T cells (Tregs) suppress exuberant immune system activation and promote immunologic tolerance. Because Tregs modulate both innate and adaptive immunity, the biomedical community has developed an intense interest in using Tregs for immunotherapy. Conditions that require clinical tolerance to improve outcomes – autoimmune disease, solid organ transplantation, and hematopoietic stem cell transplantation – may benefit from Treg immunotherapy. Investigators have designed ex vivo strategies to isolate, preserve, expand, and infuse Tregs. Protocols to manipulate Treg populations in vivo have also been considered. Barriers to clinically feasible Treg immunotherapy include Treg stability, off-cell effects, and demonstration of cell preparation purity and potency. Clinical trials involving Treg adoptive transfer to treat graft versus host disease preliminarily demonstrated the safety and efficacy of Treg immunotherapy in humans. Future work will need to confirm the safety of Treg immunotherapy and establish the efficacy of specific Treg subsets for the treatment of immune-mediated disease.